Analisis Makna dan Jenis Makna dalam Cerita Pendek “الصندوق” Karya Majed Sulaiman - Faishal Labib Nufa, Muhammad (Kajian Bahasa dan Sastra (KABASTRA), 2025)
This study analyzes the meanings in the short story “الصندوق” (The Box) by Majed Sulaiman using a semantic approach. The research applies a descriptive qualitative method based on the theories of Leech, Palmer, and Chaer, focusing on lexical, denotative, connotative, and contextual meanings. The results show that each word in the story carries deep meaning. The word “صندوق” (box), for example, literally means a container but symbolically represents love, memory, and family bonds. The author delivers moral values through simple yet meaningful language. This study concludes that semantic analysis helps reveal the moral and emotional messages in Arabic literary works, especially in children’s stories.